TOWARDS AN INTEGRATIVE PSYCHO-SPIRITUAL FRAMEWORK: EXPLORING THE COMMON GROUND BETWEEN NAFS AL-MUṬMA’INNAH AND MINDFULNESS IN THE CONTEXT OF PSYCHOLOGICAL WELL-BEING - Ansori, Ikhwan; Purnama, Davik Ihsan (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2025)
This study discusses the concept of nafs al-muṭma’innah in the Qur'an and its relationship with the psychology of mindfulness, which is rapidly developing in the modern world. This study aims to explore how the Qur'an explains peace of mind not merely as a stable emotional state, but as a spiritual awareness centered on Allah. Using a descriptive qualitative method based on thematic analysis of Qur'anic verses, this paper explores the process of achieving peace of mind through four main paths: tazkiyatun nafs (purification of the self), dzikrullah (remembrance of Allah), prayer (inner communication with God), and tawakkal (total surrender). This study shows that nafs al-muṭma'innah is the highest form of spiritual health that also has a direct impact on human psychological and social balance. From a contemporary psychological perspective, this state is similar to mindfulness, which is full awareness of the present reality, but differs in orientation: while mindfulness is self-centered awareness, nafs al-muṭma’innah is God-centered awareness. Through a dialogue between the Qur'an and modern psychology, this paper seeks to reaffirm the importance of spiritual values in the healing of the soul and the search for meaning in the lives of people today.